Emprego de ma teriais rest auradores adesivos direto no ângulo incisal de incisivos centrais fra turados - Okida, Ricardo Coelho [UNESP]; Okida, Daniela Secches da Silveira; Machado, Lucas Silveira [UNESP] (My University, 2012)
A case report of a patient who presents as chief complaint presence of stained restorations in the anterior teeth. After analysis and discussion of the clinical therapeutic approaches to be adopted, it was observed the presence of type class IV restorations on teeth 11 and 21, due to an oblique coronal fracture in the past. But the patient was not satisfied with the aesthetic result, then where was planned the realization of the removal of the restorations, for subsequently be used direct restorative materials for the correction of form, function and esthetics. The final result showed that the restorations were able to return the form, function and aesthetic dental, thereby evidencing the proven development of restorative dentistry in the solution of aesthetic problems.

Relato de caso clínico de paciente que apresentava como queixa principal a presença de restaurações manchadas na região anterior de seus dentes. Após meticulosas análises clínicas e discussões das condutas terapêuticas a serem adotadas, foi observado a presença de restaurações tipo classe IV nos dentes 11 e 21, em decorrência de uma fratura coronária oblíqua no passado. Porém o paciente não estava satisfeito com o resultado estético das mesmas, onde então foi planejado a realização da remoção das restaurações com ponta diamantada, para posteriormente ser utilizado materiais restauradores diretos para a correção da forma, função e estética dos dentes envolvidos na restauração. Como resultado final, observou-se que as resinas compostas foram capazes de devolver a forma, a função e a estética dental de maneira satisfatória, possibilitando o paciente à satisfação de sorrir novamente.
Direct adhesive restoration of anterior teeth with central fractured incisors
Keywords: Dental bonding; Composite resins; Esthetics; Resinas compostas; Estética dentaria; Adesivos dentários